Australia Felix : landscapes - Makin, Jeffrey, 1943-; Olsen, John, 1928-2023; Zimmer, Jenny, 1941-; Heathcote, Christopher, 1959- (South Yarra, Vic. : Macmillan Art Publishing, 2002)
The paintings of Jeffrey Makin, artist, academic and long term art critic for Melbourne's Sun-Herald, are featured in this lavishly illustrated monograph. In his introduction, Christopher Heathcote describes Makin's approach to landscape painting and his treatment of some of Australia's most dramatic landscape features.
Includes bibliographical references.
Keywords: Makin, Jeffrey, -- 1943-; Landscape painting, Australian; Australia -- In art